Factors associated with falls in Japanese polio survivors. Issue 13 (18th June 2020) - Imoto, Daisuke; Sawada, Koshiro; Horii, Motoyuki; Hayashi, Kazuya; Yokota, Motomi; Toda, Fumi; Saitoh, Eiichi; Mikami, Yasuo; Kubo, Toshikazu
Abstract: Purpose: To identify factors associated with falls in Japanese polio survivors and assess the extent of their impact. Materials and methods: Subjects were 128 polio survivors. Fall history and fear of falling, lower limb muscle strength, gait ability (determined by walking speed and number of steps per day), post-polio syndrome incidence, and orthosis or walking aid use were assessed, and factors associated with falls were identified using logistic regression analysis. Results: The fall rate was 64%. Fallers (subjects with one or more falls in the preceding 12 months) had low lower limb muscle strength, slow walking speed, high total scores on the Fall Efficacy Scale-International, which assesses fear of falling, and a high orthosis use rate. Knee extension muscle strength on the weaker side was identified as a main factor influencing risk of falls (odds ratio: 0.72, 95% confidence interval: 0.56–0.96). Receiver operating characteristic curve analysis gave a cutoff value for knee extension muscle strength on the weaker side of 0.42 N/kg or lower. Conclusion: Low knee extension muscle strength on the weaker side was associated with falls, but predictive ability using a single internal factor might be poor. It appears that a comprehensive examination, including other factors, is required. Implications for rehabilitation: As polio survivors age, their risk of falling increases. To identify polio survivors who are at risk of falls, it is important to determine the factors associated with falls and their influence on fall risk. The results of this study showed that reduced knee extension muscle strength on the weaker side was a risk factor for falls in polio survivors. To precisely predict the risk of falls in polio survivors, a comprehensive evaluation of both internal and external factors is required.